O lugar da Matemática na educação infantil: um estudo sobre as atitudes e crenças de autoeficácia das professoras no trabalho com as crianças - Tortora, Evandro (2019)
This research aimed to answer the following research question: "What are the possible relationships between beliefs of self-efficacy at work with mathematical knowledge, attitudes towards mathematics and the teaching practice in early childhood education?". This study was developed in the light of psychology assumptions, such as Bandura's Social Cognitive Theory (1986, 1989, 2008) and research on Brito's Attitudes (1996), and researchers in Mathematics Education, such as Lorenzato (2008). This study included 115 teachers of early childhood education. The instruments used in this study were: 1) a self-efficacy scale on working with mathematics in early childhood education, built and validated for this study; 2) a scale of attitudes toward mathematics for preschool teachers adapted for this study; 3) a questionnaire; 4) a semi-structured interview; 5) a field diary for systematic observation of teachers' practices with children. In total, 115 teachers answered both scales, of which 55 answered the questionnaire. Among this group, two teachers gave the interview and authorized the researcher to participate in their activities with the children. The analysis of the data showed that: 1) Most teachers have positive self-efficacy beliefs about working with mathematics, whose main source is direct experience and vicarious experience. Vicarious experience and social persuasion are considered most influential in forming positive self-efficacy beliefs; 2) Most teachers have attitudes that tend to be positive about math; 3) there is a moderate, positive and significant correlation between self-efficacy beliefs in working with mathematics in early childhood education and attitudes toward mathematics; 4) Positive experiences in relation to mathematics seem to have more strength in the formation of teachers' self-efficacy attitudes and beliefs, as they seek to overcome negative practices experienced by them as students; 5) The teachers declared a selfefficacy in problem solving work, however, a qualitative analysis of the questionnaires and interviews showed that the idea of "problem" for the teachers is linked to everyday situations or questions to be answered. The “challenging” character of the problem was considered by approximately half of the teachers; 6) Interviews show that teachers have self-efficacy beliefs and positive attitudes and this reflects how they plan children's interactions with mathematical knowledge; 7-) Observations of teachers 'practices illustrate the problematic posture that mathematics can be worked on in early childhood education. In addition, teachers' positive attitudes and beliefs show an openness to dialogue about their practice and constant concern for learning new forms of interaction. with math in kindergarten. However, both teachers lack training to enable experiences that involve greater autonomy of children in exploring the times, spaces and resources used to develop mental processes necessary for learning mathematical concepts.